Brazilian Dialysis Survey 2023 - Fabiana B. Nerbass; Helbert do Nascimento Lima; Jorge P. Strogoff-de-Matos; Bruno Zawadzki; José A. Moura-Neto; Jocemir Ronaldo Lugon; Ricardo Sesso (Brazilian Journal of Nephrology)
Abstract Introduction: The annual Brazilian Dialysis Survey (BDS) supports and contributes to the development of national health policies. Objective: To report the 2023 epidemiological data from the BDS of the Brazilian Society of Nephrology (BSN). Methods: A survey was carried out in a voluntary sample of Brazilian chronic dialysis centers using an online questionnaire covering clinical and epidemiological aspects of patients on chronic dialysis, and characteristics of dialysis centers. For estimates of prevalence, incidence, and source of payment for dialysis, data were obtained from a random sample of dialysis centers. Results: A total of 37.5% (n = 332) of the centers voluntarily responded to the online questionnaire, and 124 were randomly selected for specific estimates of prevalence and incidence rates. It was estimated that on July 1, 2023, the total number of patients on dialysis was 157,357 and 51,153 started dialysis in 2023. The estimated prevalence and incidence rates of patients per million population (pmp) were 771 and 251, respectively. Of the prevalent patients, 88.2% were on hemodialysis, 8.0% on hemodialfiltration, and 3.8% on peritoneal dialysis. The prevalence of anemia (Hb <10g/dL) was 29% and hyperphosphatemia (P >5.5mg/dL), 30%. There was an increase in the frequency of use of cinacalcet and paricalcitol. The estimated overall crude annual mortality rate was 16.2%. Conclusions: Estimates from a random sample of dialysis facilities show that the absolute number and the prevalence rate of patients on chronic dialysis continue to increase. A growing number of patients were undergoing hemodiafiltration and using cinacalcet and paricalcitol for hyperparathyroidism treatment.